Structure of Mahmud Zamakhari’s Work “Nukatu-L-I’rab” - Abzalova Farida (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2024)
This article briefly describes the life and scientific activity of Zamakhshari. It also provides information about the scholar's work "Nukatu-l-i'rab". The author analyzes the importance of this work as part of the scholar’s scientific heritage. The article discusses the role of "Nukatu-l-i'rab" in linguistics and its relevance today. Copies of the work preserved in libraries around the world are also mentioned.